2017
DOI: 10.1080/10095020.2017.1399675
|View full text |Cite
|
Sign up to set email alerts
|

Routing through open spaces – A performance comparison of algorithms

Abstract: Finding the shortest path through open spaces is a well-known challenge for pedestrian routing engines. A common solution is routing on the open space boundary, which causes in most cases an unnecessarily long route. A possible alternative is to create a subgraph within the open space. This paper assesses this approach and investigates its implications for routing engines. A number of algorithms (Grid, Spider-Grid, Visibility, Delaunay, Voronoi, Skeleton) have been evaluated by four different criteria: (i) Num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Furthermore, it is widely accepted in the literature [83,84] that these open spaces provide visual access to the building which facilitates the legibility of the building [85] and orientation [86]. In contrast, this freedom of movement induces difficulties in modeling open spaces and modeling the routing in these spaces, which have been outlined and examined in a number of studies (e.g., [87,88]).…”
Section: Indoor Navigation Situationsmentioning
confidence: 99%
“…Furthermore, it is widely accepted in the literature [83,84] that these open spaces provide visual access to the building which facilitates the legibility of the building [85] and orientation [86]. In contrast, this freedom of movement induces difficulties in modeling open spaces and modeling the routing in these spaces, which have been outlined and examined in a number of studies (e.g., [87,88]).…”
Section: Indoor Navigation Situationsmentioning
confidence: 99%
“…For future studies, the following items are suggested based on the main limitations of the research. Heuristic and metaheuristic methods may be implemented to solve the problem in large scales efficiently, eg, as proposed by Song and Cheng, Hahmann et al, Babaee Tirkolaee et al, Goli et al, Tirkolaee et al, and Sangaiah et al Other uncertainty techniques such as fuzzy theory, grey systems, and stochastic optimal control could be compared to the current robust optimization approach for evaluating different policies under various well‐known techniques. Moreover, to make the model closer to the real‐world conditions, other objective functions including distribution reliability maximization or customers' satisfaction maximization can be studied as well.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
“…The simplification of optimization concept and strategies to further inventions establishes an active area of research in the field of mathematics, science, and engineering. The term optimization also referred as mathematics‐based encoding, which is the gathering of mathematical procedures and techniques used for resolving numerical complications across diversified regions, comprising financial and business activities such as inventory control modeling, and generating of shortest route by comparing various open space procedures with respect to diverse optimization constraints and also widespread use in the timber operational industry to achieve finest cutting standards within specific bounds of machining factors . The current developments in computational advancement move away from the conventional strategies to contemporary nature inspired metaheuristic strategies.…”
Section: Introductionmentioning
confidence: 99%